Physician modified endograft to treat a symptomatic juxta-renal aortic aneurysm: report of the first case at our center - Henrique Guedes da Rocha; Luís Loureiro; Sérgio Teixeira; Carolina Vaz; Rui Machado (Angiologia e Cirurgia Vascular)
BACKGROUND: Symptomatic or ruptured juxta-renal aortic aneurysms can be managed through open surgical repair or endovascular approaches, including chimney endovascular aortic repair (chEVAR), off-the-shelf branched devices, or physician-modified endograft (PMEG). PMEG has proven to be a feasible alternative with satisfactory long-term outcomes for such conditions.